Philodendron Schott (Araceae Juss.) in the district of Carvão, Mazagão, Amapá, Brazil - Rodrigues, Plúcia Franciane Ataide; Facundes, Alessandra dos Santos; Pereira, Luciano Araujo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The present work aims to characterize and identify the species of the genus Philodendron Schott (Araceae) in the district of Carvão, Mazagão, Amapá, Brazil. Descriptions of the collected species, their taxonomic treatment, illustrations, comments, elaboration of a key to identify the species occurring in the area and data on the geographic distribution are presented. Five species were recorded in the region: Philodendron brevispathum Schott, P. linnaei Kunth, P. pedatum (Hook.) Kunth, P. pulchellum Engl., and P. acutatum Schott. The collected taxa present great morphological variety and marked heteroblasty.